Perbandingan Produktivitas Dan Kualitas Pertanian Sawi Pagoda Antara Metode Konvensional Dan Metode Digitalisasi Dengan Mesin Otomasi Hydroponik Dan Greenhouse - Eti Yulianti; Siti Ning Farida (Jurnal Kajian dan Penelitian Umum, 2023)
This study aims to compare the productivity and quality of pagoda mustard farming between conventional methods and digitalization methods using hydroponic and greenhouse automation machines. The research method used is qualitative with an interview approach and literature study. Interviews were conducted to gain an in-depth understanding of the farmer's experience, the challenges faced, and the differences in productivity and quality of agricultural output between the two methods. In addition, a literature study was conducted to collect relevant information about the advantages, limitations and effects of conventional methods and digitalization methods in pagoda mustard farming. The references used include scientific journals, books, articles and other sources of information related to the research topic. The results of this study are expected to provide a better understanding of the comparison of productivity and quality of pagoda mustard farming between conventional methods and digitalization methods with hydroponic and greenhouse automation machines. These findings can serve as a basis for farmers, researchers and practitioners in choosing the most effective and efficient method of cultivating pagoda mustard.